2002
DOI: 10.1093/ps/81.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enzymatic and Chemical Treatments on Feather Solubility and Digestibility

Abstract: This study was designed to evaluate the effect of chemical and enzymatic approaches to digest poultry feathers from dead birds for the purpose of recycling their nutrients as animal feeds. The experimental treatments were as follows: 1) control, 2) 24-h enzyme, 3) 24-h NaOH, 4) 2-h NaOH, and 5) 2-h NaOH and 24-h enzyme. The feather N solubilities of the control, 24-h enzyme, 24-h NaOH, 2-h NaOH, and 2-h NaOH and 24-h enzyme treatments were 0.91, 2.55, 78.83, 30.03, and 50.34%, respectively. The pepsin digestib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 9 publications
2
18
0
2
Order By: Relevance
“…Earlier researchers reported that B. licheniformis can utilized to degrade keratin containing waste from poultry forms by producing keratin degrading enzyme (keratinase) for making animal feed and manure [2][3][4]. Keratins are made up two main subunits such as alpha and beta keratins which composed various amino acids [5]. The feathers are mainly composed of beta-keratin [6,7].…”
Section: Editorialmentioning
confidence: 99%
“…Earlier researchers reported that B. licheniformis can utilized to degrade keratin containing waste from poultry forms by producing keratin degrading enzyme (keratinase) for making animal feed and manure [2][3][4]. Keratins are made up two main subunits such as alpha and beta keratins which composed various amino acids [5]. The feathers are mainly composed of beta-keratin [6,7].…”
Section: Editorialmentioning
confidence: 99%
“…The higher alkalinity is attributed to deamination reactions leading to the release of ammonium and thus increase in pH and consequent increase in keratinolysis. In addition, the keratinases are generally stimulated in the presence of divalent metal ions like Mg 2+ [30][31][32][33][34].…”
Section: Optimization the Nutritional Requirements Of B Sphaericusmentioning
confidence: 99%
“…It allows for production of feather meal of improved dietary value, amino acid balance and digestibility [14,18]. Occasionally, combined chemical and enzymatic hydrolysis also proves to be advantageous [10,19]. Bacteria-mediated keratin breakdown is known to be a cumulative effect of proteolytic cleavage as well as auxiliary reducing factors, including released reduced thiols or indigenous disulfide reductase enzymes [20,21].…”
Section: Introductionmentioning
confidence: 99%